Description of a novel HLA null allele, DRB1*15:176N. (28th August 2019) - Balas, Antonio; Alenda, Raquel; Moreno‐Hidalgo, Miguel A.; García‐Sánchez, Felix; Vicario, José L.
Abstract : A new HLA null allele, DRB1*15:176N, was characterized in a Spanish volunteer bone marrow donor.